Enhanced Light Response Performance of Ceria-Based Composites with Rich Oxygen Vacancy - Yanping Li; Xue Bian; Hui Dong; Hongtao Chang; Wenyuan Wu (Molecules)
Increasing the concentration of oxygen vacancies in ceria-based materials to solve the bottleneck of their applications in various fields has always been a research hotspot. In this paper, ceria-based cerium–oxygen–sulfur (Ce-O-S) composites that were composed of CeO2, Ce4O4S3, and Ce2(SO4)3 were synthesized by a precipitation method. The compositional, structural, morphological, and light response characteristics of prepared Ce-O-S composites were investigated by various characterization techniques. The molar ratio of oxygen vacancies to lattice oxygen can reach a maximum of 1.83 with Ce-O-S composites. The band gap values of the Ce-O-S composites were less than 3.00 eV, and the minimum value was 2.89 eV (at pH 12), which successfully extended the light response range from the ultraviolet light region to the short-wave blue light region. The remarkable light response performance of Ce-O-S composites can be mainly attributed to the high proportion of oxygen vacancy. Moreover, the higher proportion of oxygen vacancies can be attributed to the doping of Ce (+3) and S (−2) in the lattice of CeO2, and the synergistic effect of CeO2, Ce4O4S3, and Ce2(SO4)3. Moreover, the ceria-based Ce-O-S composites with rich oxygen vacancy in this research can be applied in light blocking, photocatalysis, and other related fields.